Polycyclic aromatic hydrocarbon degrading bacteria from the Indonesian Marine Environment - ELVI YETTI; AHMAD THONTOWI; YOPI YOPI (Society for Indonesian Biodiversity, 2016)
Yetti E, Thontowi A, Yopi. 2016. Polyaromatic hydrocarbon degrading bacteria from the Indonesian Marine Environment.Biodiversitas 17: 857-864. Oil spills are one of the main causes of pollution in marine environments. Oil degrading bacteria play an important role for bioremediation of oil spill in environment. We collected 132 isolates of marine bacteria isolated from several Indonesia marine areas, i.e. Pari Island, Jakarta, Kamal Port, East Java and Cilacap Bay, Central Java. These isolates were screened for capability to degrade polyaromatic hydrocarbons (PAHs). Selection test were carried out qualitatively using sublimation method and growth assay of the isolates on several PAHs i.e. phenanthrene, dibenzothiophene, fluorene, naphtalene, phenotiazine, and pyrene. The fifty-eight isolates indicated in having capability to degrade PAHs, consisted of 25 isolates were positive on naphthalene (nap) and 20 isolates showed ability to grow in phenanthrene (phen) containing media. Further, 38 isolates were selected for dibenzothiophene (dbt) degradation and 25 isolates were positive on fluorene (flr). On the other hand, 23 isolates presented capability to degrade in phenothiazine (ptz) and 15 isolates could grow in media with pyrene (pyr). Based on homology analysis of partial 16S rDNA gene, we obtained six taxonomy classes of PAH degrading bacteria, namely Î±-Proteobacteria (31%), Î³-Proteobacteria (43%), Firmicutes Bacilli (12%), Actinobacteria; Micrococcales (9%), Actinobacteria; Propionibacteriales (2%), and Bacteroidetes; Flavobacteriia (3%). In this research, we obtained diverse PAH degrading bacteria from marine areas.